PENGARUH MANAJEMEN LINEN TERHADAP KINERJA ROOMBOY DI HOTEL HARRIS BATAM CENTER - Gemilang, Gilang (RC-INSTITUT, 2019)
This study aims to analyze the influence of linen management on roomboy performance at the Harris Hotel Batam Center. This type of research is classified into causal research associations. The population in this study was all roomboys at Harris Batam Center hotel. The research sample amounted to 30 people with a sampling technique that was saturated sample. The data collection technique is done by using a questionnaire (questionnaire) with a Likert scale that has been tested for validity and reliability. Furthermore, the data were analyzed through description analysis and simple linear regression with the help of SPSS version 16.00 computer program. The results showed that: 1) Management of linen at the Batam Center Harris Hotel was very poor with the highest percentage test of 30%. 2) Roomboy performance at Harris Batam Center hotel is classified as very bad category with the highest percentage value of 33.33%. 3) Simple linear regression hypothesis test results obtained by R Square of 0.649, meaning that linen management affects roomboy performance by 64.9%, and 35.1% is influenced by other factors outside of this study. So the hypothesis proposed is that there is a significant influence between linen management on roomboy performance.